2014
DOI: 10.2133/dmpk.dmpk-13-rv-032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cytochrome P450, Family 2, Subfamily D, Polypeptide 6 (CYP2D6) Polymorphisms on Pain Sensitivity and Clinical Response to Weak Opioid Analgesics

Abstract: CYP2D6 polymorphisms show large geographical and interethnic differences. Variations in CYP2D6 activity may impact upon a patient's pain level and may contribute to interindividual variations in the response to opioids. This paper reviews the evidence on how CYP2D6 polymorphisms might influence pain sensitivity and clinical response to codeine and tramadol. For example, it is shown that (1) CYP2D6 poor metabolizers (PMs) may be less efficient at synthesizing endogenous morphine compared with other metabolizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 101 publications
(226 reference statements)
0
27
0
Order By: Relevance
“…In addition, it is possible that CBD affects the metabolism of opioid analgesics by inhibiting CYP2D6, because polymorphism of CYP2D6 has been linked to distinct pain sensitivity and difference of response to opioid analgesics [268].…”
Section: Cbd Enzyme Targets In Painmentioning
confidence: 99%
“…In addition, it is possible that CBD affects the metabolism of opioid analgesics by inhibiting CYP2D6, because polymorphism of CYP2D6 has been linked to distinct pain sensitivity and difference of response to opioid analgesics [268].…”
Section: Cbd Enzyme Targets In Painmentioning
confidence: 99%
“…These patients may, however, be at a greater risk of respiratory depression at standard doses compared to normal metabolizers 12,18. However, data demonstrating associations between CYP2D6 phenotype and poor pain control have been mixed 13,16. Several studies have indicated that persons with a poor metabolizer phenotype experience less pain relief from codeine and tramadol,1925 but the effect of a poor metabolizer phenotype on pain relief from oxycodone and hydrocodone is less clear 2630.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that persons with a poor metabolizer phenotype experience less pain relief from codeine and tramadol,1925 but the effect of a poor metabolizer phenotype on pain relief from oxycodone and hydrocodone is less clear 2630. In addition, the impact of CYP2D6 variants on mild, nonlife threatening, adverse reactions associated with opioids (e.g., nausea), and subsequent effects on pain control due to intolerance, has not been routinely studied 16. A larger study of cancer patients found no differences in pain control, nausea, or tiredness among poor, normal, and ultrarapid metabolizers taking oxycodone 30.…”
Section: Introductionmentioning
confidence: 99%
“…4, 5 M1 has a higher affinity (Ki=3.4 nM) for the mu-opioid receptor compared to the parent compound (Ki=2.4 µM) 6 , highlighting the importance of M conversion by CYP2D6. The relevance of CYP2D6 genetics for M has been established in the adult population 4,7,8 and in neonates 9 , implicating decreased concentrations of the active metabolite and an absence of analgesia. However, the variation in disposition of M extends beyond this conversion in M1.…”
Section: Introductionmentioning
confidence: 99%